БОБУР ЛИРИКАСИДА ИФОДАНИНГ МАЪНО ҚАТЛАМЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article philosophical peculiarities and variousity of meanings of Bobur poems are considered.